The Primacy of Index in Naming Paradigms. Part II - West, Donna E. E. (Respectus Philologicus, 2015)
This analysis highlights the semiotic naming differences between the pronouns, nouns, and verbs. It capitalizes on the role of Peirce’s Object in assigning names and the special character of pronouns and verbs to hasten notice of Objects. It showcases Peirce’s indexical sign as an individuating instrument, by arguing that nouns do not name the Object uniquely. The invoking notice of shifting places via pronouns/verbs is paramount. Naming begins with the most pure Indexes (pronouns), then nouns (which draw upon similar features); afterward, verbs emerge to name the dynamic event profile, illustrating the indispensability of the index. The advances in deictic individuation establish and reinforce the joint attentional ventures: co-signers are compelled not merely to attend to the same Object but to recognize distinctive participant roles in events as well.
Keywords: Index; Naming; Verbs; Pronouns; Peirce